THE EUROPEAN UNION’S ROLE AS AN INTERNATIONAL ACTOR IN THE ACEH MONITORING MISSION - indriana kartini (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2017)
The European Union (EU) involvement in the Aceh Monitoring Mission (AMM) was one of the successful story in the peaceful conflict settlement. In this mission, the EU has been able to show the world that it is one of significant actor in international politics. Admittedly, the EU represents uncertain image in international politics as if it can not be seen at the same level of sovereign-states. This article examines whether the EU played a significant role as an international actor in the peace process in Aceh through an indepth-look at the work of the AMM. By viewing the EU as an evolving entity which engaged in particular issues and by addressing its international presence in the context of its involvement in the AMM, it can be concluded the EU has played significant role as an international actor. Keywords: the European Union, international actor, the Aceh Monitoring Mission (AMM), Gerakan Aceh Merdeka (GAM) AbstrakKeterlibatan Uni Eropa (UE) dalam Aceh Monitoring Mission (AMM) merupakan salah satu cerita sukses dalam penyelesaian konflik secara damai. Dalam misi ini, UE mampu menunjukkan kepada dunia bahwa mereka merupakan salah satu aktor signifikan dalam politik internasional. Harus diakui bahwa UE merepresentasikan uncertain image (gambaran yang kurang jelas) dalam politik internasional yang tingkatannya tidak dapat disejajarkan dengan negara-bangsa. Artikel ini menganalisis apakah UE memainkan peran signifikan sebagai aktor internasional dalam proses perdamaian di Aceh melalui pendalaman terhadap kerja AMM. Dengan memandang UE sebagai entitas yang terlibat dalam isu-isu khusus dan dengan menekankan pada kehadiran UE di kancah internasional melalui keterlibatannya dalam AMM, maka dapat disimpulkan bahwa UE memainkan peran siginifikan sebagai aktor internasional.Kata kunci: Uni Eropa, aktor internasional, Aceh Monitoring Mission (AMM), Gerakan Aceh Merdeka (GAM)